Gambaran Ketepatan Waktu Pengembalian Rekam Medis Rawat Inap di RSUP Dr. Sitanala Kota Tangerang - Yoga Septian Bayu Ariyanto; Nanda Aula Rumana; Noor Yulia; Daniel Happy Putra (Yayasan Literasi Sains Indonesia, 2022)
Medical record is a file that contains records and documents of patient identity, examination, treatment, actions and other services that have been provided by doctors to patients. One of the factors that support medical record services is the return of medical records. Based on hospital policies that have been established inpatient medical records at RSUP Dr. Sitanala Tangerang City must return 1 x 24 hours after the patient returns home. The method used in this research is quantitative descriptive method and the data collection technique uses observation and interviews. Sampling in this study used a non-random sampling method by means of convenience sampling or no special criteria by selecting which medical records were encountered by the researcher. Based on the results of the study, it was found that 77 medical records (22.6%) were on time and 264 medical records (77.4%) were not returned on time, with an average return time of 9 x 24 hours. The factor that causes the inaccuracy of returning medical records is due to doctors who have not filled out the patient's medical resume. So it was concluded that the return of medical records was not in accordance with the guidelines set by the hospital. For this reason, there must be a new policy and sanctions that regulate the return of medical records for the sake of quality of service and the return of medical records can be returned on time.